Rethinking How Laws Are Made: Indonesia’s Legal Method Dilemma - Al-Fatih, Sholahuddin; Shahzad, Sayed Khalid (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
This study analyzes the challenges in Indonesia’s law-making process, focusing on how poorly chosen drafting methods affect the quality of regulations. As a state governed by law, Indonesia relies on written legislation, which the Law on the Establishment of Legislation regulates. However, this law fails to provide clear direction on selecting the most effective law-making methods, leading to inconsistencies in legal outcomes. In response, this research adopts a conceptual and normative approach to examine various drafting techniques—Regulatory Impact Analysis (RIA), the ROCCIPI method, the omnibus law approach, and the potential use of artificial intelligence (AI). The study reviews legal documents and case examples, and evaluates the effectiveness of these methods by assessing the output and outcome of selected regulations. The findings show that the omnibus law model works well for codifying laws around specific themes, RIA strengthens economic lawmaking through evidence-based analysis, and the ROCCIPI method suits the drafting of regional regulations. The study also finds that AI can enhance the development of academic manuscripts in the legislative drafting process. Based on these findings, the study recommends amending the Law on the Establishment of Legislation to formally incorporate RIA and ROCCIPI methods and to provide guidelines for using AI in legal drafting. By adopting a more integrated and strategic approach, Indonesia can improve the quality, coherence, and responsiveness of its legal system.